Financial Transformation? Integrating Environmental Sutainability through Green Sukuk as a Means for Sustainable Development in Indonesia - Rosdita Indah Yuniawati; Lilik Purwanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines Green Sukuk in Indonesia through a postmodern analysis approach, focusing on sustainability in Islamic finance. Utilizing a literature review method, this research gathers and analyzes relevant academic sources to understand how Green Sukuk has been integrated into the framework of Islamic finance and how it contributes to environmental sustainability goals. This study critiques traditional views and meta-narratives in conventional finance and explores how Green Sukuk reflects the sustainability values embedded in the culture and financial practices in Indonesia. The analysis shows that Green Sukuk represents a unique synthesis between Sharia principles and sustainability aspirations, offering a new perspective in both global and local financial discourse. Through a postmodern lens, this research highlights the importance of cultural and religious contexts in the interpretation and implementation of sustainable finance, and provides recommendations for further research that can deepen this integration. In a global financial framework that increasingly emphasizes sustainability issues, Green Sukuk has emerged as a significant innovation in Islamic finance that links Islamic investment principles with the urgent needs of sustainable development.